Free Your Mind, Not Your Flap. Issue 6 (15th June 2022) - Neusner, Alexander D.; Pribaz, Julian J.; Guo, Lifei
Abstract : Summary: The pedicled flap has been a mainstay of soft tissue reconstruction since the earliest days of plastic surgery. Advances in surgical technology and skill have led to an erosion in the use of pedicled flaps in favor of increasingly popular free tissue transfers. Still, regional flaps without microvascular anastomosis remain a valuable reconstructive tool. Although still requiring microsurgical skills, these flaps are of particular benefit in patients with few or poor quality recipient vessels, in those who cannot tolerate antiplatelet therapy, and in those who cannot tolerate the often-extended anesthesia time necessitated by microvascular anastomosis. Furthermore, pedicled flaps may significantly reduce total cost of a reconstruction procedure with similar outcomes. In this case series, we report challenging scenarios where microsurgical approaches may have been typical choices but were instead reconstructed by pedicled options with desired outcomes. Difficult soft tissue defects were successfully reconstructed with a variety of pedicled flaps. Soft tissue transfers to the abdomen, flank, shoulder, and back are presented. None of the reconstructions required microvascular anastomosis.